2018
DOI: 10.1002/slct.201800062
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopic and Fibroblast Activation Protein (FAP)‐Responsive Properties of Phthalocyanine‐Doxorubicin Conjugates

Abstract: A series of novel phthalocyanine‐doxorubicin (Pc‐DOX) conjugates have been prepared with a fibroblast activation protein (FAP)‐sensitive linker of glycine‐proline (Gly‐Pro) dipeptide. Meanwhile, two Pc‐DOX conjugates (1 c and 3 c) without FAP‐sensitive linker have also been prepared for comparison. For Pc‐DOX conjugates, the photosensitizing properties of the phthalocyanines are partly quenched after being conjugated with DOX. The aggregation behavior of these conjugates is less affected by the surfactant of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Huang expanded on this work by comparing both the prodrug and the traditional conjugates whilst also investigating the effects of chain length between the two components and the location of DOX on the Pc macrocycle (axial vs. peripheral) (A3-A6). [61] FAP responsiveness experiments showed that the prodrugs undergo facile enzymolysis of the linker to release the DOX unit. [61] In the absence of in vitro or in vivo testing it is difficult to accurately state which linker length or difference between axial or peripheral location of the DOX moiety provided the best overall synergistic effect.…”
Section: Phthalocyanine-anthracycline Conjugatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Huang expanded on this work by comparing both the prodrug and the traditional conjugates whilst also investigating the effects of chain length between the two components and the location of DOX on the Pc macrocycle (axial vs. peripheral) (A3-A6). [61] FAP responsiveness experiments showed that the prodrugs undergo facile enzymolysis of the linker to release the DOX unit. [61] In the absence of in vitro or in vivo testing it is difficult to accurately state which linker length or difference between axial or peripheral location of the DOX moiety provided the best overall synergistic effect.…”
Section: Phthalocyanine-anthracycline Conjugatesmentioning
confidence: 99%
“…[61] FAP responsiveness experiments showed that the prodrugs undergo facile enzymolysis of the linker to release the DOX unit. [61] In the absence of in vitro or in vivo testing it is difficult to accurately state which linker length or difference between axial or peripheral location of the DOX moiety provided the best overall synergistic effect. The photophysical data indicated that the presence of the DOX moiety did reduce Φ Δ values of both the prodrug and traditional conjugates, with the free Pc displaying higher Φ Δ values on all occasions (Table 3).…”
Section: Phthalocyanine-anthracycline Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…[61] FAP responsiveness experiments showed that the prodrugs undergo facile enzymolysis of the linker to release the DOX unit. [61] In the absence of in vitro or in vivo testing it is difficult to accurately state which linker length or difference between axial or peripheral location of the DOX moiety provided the best overall synergistic effect. The photophysical data indicated that the presence of the DOX moiety did reduce ΦΔ of both the prodrug and traditional conjugates, with the free Pc displaying higher ΦΔ on all occasions (Table 3).…”
Section: Phthalocyanine-anthracycline Conjugatesmentioning
confidence: 99%
“…The photophysical data indicated that the presence of the DOX moiety did reduce ΦΔ of both the prodrug and traditional conjugates, with the free Pc displaying higher ΦΔ on all occasions (Table 3). [61] The traditional conjugates with shorter chain lengths and peripheral conjugation sites displayed greater ΦΔ and Φfl, [61] although it is not known if this translates to better PDT performance. The development of highly effective Pc-DOX conjugates displaying limited dark toxicity in conjunction with a strong PDT response still requires additional exploration.…”
Section: Phthalocyanine-anthracycline Conjugatesmentioning
confidence: 99%